Pengaruh Kualitas Kehidupan Kerja Terhadap Kepuasan Kerja Karyawan pada PT. Pelindo IV (Persero) Cabang Terminal Petikemas Makassar - Zittaian Amelia; Uhud Darmawan Natsir; Tenri S.P. Dipoatmodjo; Agung Widhi Kurniawan; Zainal Ruma (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2023)
This study aims to investigate the effect of Quality of Work Life on Employee Job Satisfaction at PT. Pelindo IV (Persero) Makassar Container Terminal Branch. This study uses a quantitative approach with survey methods and associative research designs. The research sample consisted of 60 employees of PT. Pelindo IV (Persero) Makassar Container Terminal Branch. The data used in this study consisted of primary data and secondary data obtained through observation, interviews, questionnaires and documentation. Data analysis was performed using simple linear regression. The results of the research after the data were processed using SPSS software showed that the Quality of Work Life has a positive and significant influence on Employee Job Satisfaction at PT. Pelindo IV (Persero) Makassar Container Terminal Branch. The simple regression equation used is Y = 27,905 + 0,292, and the relationship is significant with a p-value of 0.000, which is less than the specified level of significance (0.05). In addition, the t-count value of 2.080 is also greater than the t-table value of 2.000. Furthermore, the R Square value of 0.069 indicates that the Quality of Work Life variable contributes an influence of 6.9%, while the remaining 93.1% is influenced by other variables not examined in this study.